Chitosan Oligosaccharides Regulate the Occurrence and Development of Enteritis in a Human Gut-On-a-Chip - Jing, Bolin; Xia, Kun; Zhang, Chen; Jiao, Siming; Zhu, Limeng; Wei, Jinhua; Wang, Zhuo A.; Chen, Nannan; Tu, Pengfei; Li, Jianjun; Du, Yuguang (Frontiers in Cell and Developmental Biology, 2022)
Past studies on the protective effects of chitosan oligosaccharides (COS) on inflammatory bowel diseas (IBD) commonly rely on animal models, because traditional cell culture systems couldn’t faithfully mimic human intestinal physiology. Here a novel human gut-on-a-chip microsystem was established to further explore the regulatory effects of COS on the occurrence and development of human enteritis. By constructing an intestinal injury model caused by dextran sodium sulfate (DSS) on the chip, this study proved that COS can reduce intestinal epithelial injury by promoting the expression of the mucous layer for the first time. By establishing an inflammatory bowel disease model on the chip caused by E. coli 11775, this study demonstrated that COS can protect the intestinal epithelial barrier and vascular endothelial barrier by inhibiting the adhesion and invasion of E. coli 11775 for the first time. In addition, similar to the results in vivo, COS can decrease the inflammatory response by reducing the expression of toll-like receptor 4 protein and reducing the nuclear DNA binding rate of nuclear factor kappa-B protein on this chip. In summary, COS can be used as a potential drug to treat human IBD and the human gut-on-a-chip would be used as a platform for quick screening drugs to treat human IBD in future.